2019
DOI: 10.1177/0961203319889663
|View full text |Cite
|
Sign up to set email alerts
|

Familial lupus in Tunisia: a series of 14 families

Abstract: The relatively high prevalence of systemic lupus erythematosus (SLE) in familial cases supports genetic susceptibility to this disease. Although many advances have been made in the identification of new genes implicated in lupus pathogenesis, to date, there has been no large study of familial SLE. We report what we believe to be the first study of familial SLE in the North African population. The objectives of this study were to determine the main clinical and laboratory features of familial lupus and to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Most cases in the CYC group were class IV (59,1%), with (40.9%) class III, while most cases in the MMF group were class IV (75%), with (25%) class III (p<0.05). Most cases had a chronicity index (1)(2)(3)(4)(5)(6), in (82.5%) of the CYC group, versus (76.9%) of the MMF group (p<0.05). For maintenance therapy after induction, most of the CYC group (78.8%) used azathioprine (AZA), while (94.2%) of the MMF group used MMF (p<0.05) (Table 1).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Most cases in the CYC group were class IV (59,1%), with (40.9%) class III, while most cases in the MMF group were class IV (75%), with (25%) class III (p<0.05). Most cases had a chronicity index (1)(2)(3)(4)(5)(6), in (82.5%) of the CYC group, versus (76.9%) of the MMF group (p<0.05). For maintenance therapy after induction, most of the CYC group (78.8%) used azathioprine (AZA), while (94.2%) of the MMF group used MMF (p<0.05) (Table 1).…”
Section: Discussionmentioning
confidence: 96%
“…ystemic lupus erythematosus (SLE) is a multisystem, autoimmune disease [1], and diagnosis is made on history, examination, and autoantibodies like anti-neutrophil antibodies (ANA), and anti-double-stranded DNA (anti-ds-DNA) may be positive [2].…”
Section: Introductionmentioning
confidence: 99%
“…16 Regarding sSS, the frequency in patients with RA ranged from 4.3% in a cross-sectional study conducted in Morocco during 2007-2011 and including 164 patients, 20 to 100% in the aforementioned study from Senegal, which included only 4 RA patients. 16 The frequency of SS in patients with SLE was 11.1% in a retrospective cross-sectional study from Tunisia conducted during 1996-2014 and including 27 subjects, 30 whereas that of SS in patients with autoimmune hepatitis was 8% in a retrospective cross-sectional study from Tunisia involving 83 patients and conducted between 1996 and 2004. 15 There was no population-based incidence or prevalence of SS in Africa.…”
Section: Frequencymentioning
confidence: 99%
“…Fourteen studies reported the frequency of SS across autoimmune and other rheumatic conditions (Supplementary Table S7, http://links.lww.com/RHU/A253). 12,15,16,[18][19][20][21][24][25][26][27][29][30][31] The frequency of pSS ranged from 1.8% in a cross-sectional study from Morocco reporting data of 944 subjects with diverse autoimmune diseases recruited between 2010 and 2016, 29 to 47.6% in a cross-sectional study from Senegal reporting data of 27 subjects with systemic vasculitides recruited during 1995-2007. 16 Regarding sSS, the frequency in patients with RA ranged from 4.3% in a cross-sectional study conducted in Morocco during 2007-2011 and including 164 patients, 20 to 100% in the aforementioned study from Senegal, which included only 4 RA patients.…”
Section: Frequencymentioning
confidence: 99%
“…[3] Studies on twins and families also indicate that genetic susceptibility has a higher heritability and consistency rate in SLE families compared with sporadic populations. [4] The GWAS studies on the SLE families have been successfully applied to recognize more loci related to the susceptibility of SLE. Previous studies of our group have shown that gene polymorphisms of NF-κB (nuclear factor κB) signaling pathways were associated with SLE in a Chinese population.…”
Section: Introductionmentioning
confidence: 99%